Breaking paradigms in severe epistaxis: the importance of looking for the S-point - Kosugi,Eduardo Macoto (2018)
Abstract Introduction: Since the introduction of nasal endoscopy into the field of Otorhinolaryngology, the treatment paradigm for cases of severe epistaxis has shifted toward early and precise identification of the bleeding site. Although severe epistaxis is usually considered to arise from posterior bleeding, an arterial vascular pedicle in the superior portion of the nasal septum, around the axilla projection of the middle turbinate, posterior to the septal body, frequently has been observed. That vascular pedicle was named the Stamm's S-point. Objective: The aim of this study was to describe the S-point and report cases of severe epistaxis originating from it. Methods: A retrospective case series study was conducted. Nine patients with spontaneous severe epistaxis, where the S-point was identified as the source of bleeding, were treated between March 2016 and March 2017. Results: Male predominance (77.8%) with age average of 59.3 years old were reported. Most cases presented comorbidities (88.9%) and were not taking acetylsalicylic acid (66.7%). A predominance of left sided involvement (55.6%) and anteroposterior bleeding being the principal initial presentation (77.8%) was seen. Six patients (66.7%) presented with hemoglobin levels below 10 g/dL, and four (44.4%) required blood transfusion. Cauterization of S-point was performed in all patients, with complete resolution of bleeding. No patient experienced recurrence of severe epistaxis. Conclusion: The Stamm's S-point, a novel source of spontaneous severe epistaxis, is reported, and its cauterization was effective and safe. Otolaryngologists must actively seek this site of bleeding in cases of severe epistaxis.